Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
5Y(X-Z)=0
Step-by-step explanation:
5(WX+YZ)= 5WX+5XY
Open bracket l.h.s
5wx+ 5yz
Put like terms together
5wx-5wx= 5xy-5yz
Substitute
0=5y(x-z)
Step-by-step explanation:
5(WX+YZ)= 5WX+5XY
Open bracket l.h.s
5wx+ 5yz
Put like terms together
5wx-5wx= 5xy-5yz
Substitute
0=5y(x-z)
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.